Participatory projects and their impact on immigrants’ integration in France: Empowering by doing - Dominguez, Noémie; Mercier-Suissa, Catherine; Ottaviano, Nancy; Cascant, Eunice (Management international / International Management / Gestiòn Internacional, 2024)
Objective: We draw upon the empowerment and participatory literature to understand how participatory initiatives foster the socio-cultural and economic integration of immigrants. Our research is based on the analysis of a French housing facility located in Paris. Methodology: Data was collected through interviews with four sub-groups, observations and document analysis. Results and contributions: Our research show that participatory projects act on the psychological empowerment of immigrants. They also encourage other stakeholders to modify their habits to implement more inclusive practices. We highlighted the importance of arts as communication drivers and ways to reverse power relations. Finally, we present a process model of empowerment through participatory initiatives.